Language comprehension warps the mirror neuron system - Zarr, Noah; Ferguson, Ryan; Glenberg, Arthur M. (Frontiers in Human Neuroscience, 2013)
Is the mirror neuron system (MNS) used in language understanding? According to embodied accounts of language comprehension, understanding sentences describing actions makes use of neural mechanisms of action control, including the MNS. Consequently, repeatedly comprehending sentences describing similar actions should induce adaptation of the MNS thereby warping its use in other cognitive processes such as action recognition and prediction. To test this prediction, participants read blocks of multiple sentences where each sentence in the block described transfer of objects in a direction away or toward the reader. Following each block, adaptation was measured by having participants predict the end-point of videotaped actions. The adapting sentences disrupted prediction of actions in the same direction, but a) only for videos of biological motion, and b) only when the effector implied by the language (e.g., the hand) matched the videos. These findings are signatures of the mirror neuron system.